The Paradigm of Islamic Religious Education in the Era of Society 5.0 - Cisia Padila; Ramadhanul Ikhsan; Tegu Reski Amanah; Martin Kustati; Nana Sepriyanti (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
The paradigm of Islamic religious education in the era of Society 5.0 is an approach that integrates technology with spiritual and moral values to create relevant and holistic learning experiences. This article discusses various paradigms about the importance of global-minded Islamic religious education in facing the era of Society 5.0. This era is characterized by the digital revolution and technological developments that affect various aspects of human life such as economic, social and cultural. The approach used in this research is a qualitative research method with a focus on descriptive analysis of various written texts. The results of this study explain that Islamic religious education with a global outlook will prepare the younger generation to face multidimensional challenges presented by technological advances, global demographics, and complex social changes. As the basis of the paradigm, global-minded Islamic religious education allows the integration of religious, cultural, and moral values that are relevant to the global context. In preparing students, educators should adopt a holistic and inclusive approach. This involves teaching not only religious doctrines and rituals, but also emphasizes a deep understanding of the universality and humanistic values of Islam that can be adopted in diverse environments. Global Islamic religious education also provides a bridge in promoting peace, tolerance and intercultural understanding. Global Islamic religious education is a solution in facing the era of globalization.